A single internal telomere tract ensures meiotic spindle formation. (8th January 2013) - Tomita, Kazunori; Bez, Cécile; Fennell, Alex; Cooper, Julia Promisel
Abstract : Contact between telomeres and the fission yeast spindle pole body during meiotic prophase is crucial for subsequent spindle assembly, but the feature of telomeres that confers their ability to promote spindle formation remains mysterious. Here we show that while strains harbouring circular chromosomes devoid of telomere repeat tracts undergo aberrant meiosis with defective spindles, the insertion of a single internal telomere repeat stretch rescues the spindle defects. Moreover, the telomeric overhang‐binding protein Pot1 is dispensable for rescue of spindle formation. Hence, an inherent feature of the double‐strand telomeric region endows telomeres with the capacity to promote spindle formation. A single internal telomere tract ensures meiotic spindle formation: This study shows that a single internal telomere repeat stretch is sufficient to ensure normal meiotic spindle formation in fission yeast, indicating that an inherent feature of the telomeric region promotes spindle formation.